Silver-based reflective coatings for micromachined optical filters - Correia, J. H. (1999)
Silver films of 40 nm thickness, evaporated on a 300 nm thick low-stress silicon nitride layer, are used as high-quality mirrors operating in the visible and near IR spectral range. Application of a silicon nitride membrane under tension, placed within a square Si frame after bulk micromachining, improves the initial mirror flatness. Two parallel mirrors, each with square aperture of up to 2x2 mm2 and an electrostatically controlled spacing, form a tunable Fabry–P´erot optical filter. Investigation of the silver-based reflective coatings, and mirror characterization, including influence of bulk micromachining, are presented